2008
DOI: 10.1002/ejsp.553
|View full text |Cite
|
Sign up to set email alerts
|

Identification as an organizational anchor: how identification and job satisfaction combine to predict turnover intention

Abstract: The article examines the role of organizational identification and job satisfaction in relation to turnover intentions in seven organizations. Two models are proposed in which either job satisfaction or organizational identification was treated as a mediator of the other's relationship with turnover intention. The organizations varied in terms of culture (Japan vs. UK), and institutional domain (academic, business, health, mail, legal). Within each organization, and meta-analytically combined across the seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 78 publications
5
89
1
3
Order By: Relevance
“…This study also confirms the work by Koster et al (2009);De Moura et al (2008); Boselie and Wiele (2001); Bowen and Ostroff (2000); Clark et al (1998);and Freeman (1978) that demonstrates a negative relationship between job satisfaction and turnover intentio n: A highly satisfied employee will have a lower tendency to leave the organization, and conversely a highly dissatisfied employee is more likely to leave the organization and change employer. Furthermore, the findings of this research are partly in line with the results by Chen and Wang (2014) whose study showed a partially mediated relationship between the HR attribution of commitment focus towards turnover intention, and a fully mediated relationship between the HR attribution of control focus toward s turnover intention.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This study also confirms the work by Koster et al (2009);De Moura et al (2008); Boselie and Wiele (2001); Bowen and Ostroff (2000); Clark et al (1998);and Freeman (1978) that demonstrates a negative relationship between job satisfaction and turnover intentio n: A highly satisfied employee will have a lower tendency to leave the organization, and conversely a highly dissatisfied employee is more likely to leave the organization and change employer. Furthermore, the findings of this research are partly in line with the results by Chen and Wang (2014) whose study showed a partially mediated relationship between the HR attribution of commitment focus towards turnover intention, and a fully mediated relationship between the HR attribution of control focus toward s turnover intention.…”
Section: Resultssupporting
confidence: 88%
“…An obvious reaction to dissatisfaction is to leave the company and change employers (Clark et al 1998;De Moura et al 2008;Mahdi et al 2012), and conversely, employees who have high satisfaction levels are more motivated to stay within the company.…”
Section: Job Satisfaction As a Mediator Between Hr Attributions And Tmentioning
confidence: 99%
“…Similarly, Örücü and Özafşarlıoğlu (2013) surveyed employees' organizational justice perceptions under three dimensions. Finally, our findings on the effect of organizational identification on intention to quit concur with the survey results of van Knipenberg and van Schie (2000), Cicero and Pierro (2007), Cole and Bruch (2006), De Moura et al (2009), Turunç and Çelik (2010, and Polat and Meydan (2010).…”
Section: Discussionsupporting
confidence: 90%
“…For this reason, managers should seek ways of improving OI (Gümüs et al, 2012). They also have pointed out that variables such as work conditions, fair policies, good working relationships and participative leadership can influence employees' OI (De Moura et al, 2009). However, there is not adequate empirical studies to answer the question that "may some individuals' week OI, despite good work conditions, proper leadership style and favorable work relations, be related to their personality or not?…”
Section: Discussionmentioning
confidence: 99%